A Literature Study on Students’ Etiquette toward Teachers: Psychological, Social, and Educational Implications - Harahap, Siti Fadila (Aksara Shofa, 2025)
This study aims to examine the importance of students’ etiquette toward teachers in the educational context through a literature review approach. Good manners, such as respect, politeness, and social awareness, play a crucial role in creating an effective and harmonious learning environment. From a psychological perspective, students’ positive behavior supports teachers’ mental well-being and enhances motivation in the teaching and learning process. Conversely, negative student behavior can lead to stress and frustration among teachers. This study also highlights the significance of social interaction within the school environment from the perspective of the sociology of education, particularly through the theories of symbolic interactionism and labeling, which suggest that everyday interactions between students and teachers shape social identity and influence students’ academic performance. The research method used is a literature review, aimed at synthesizing knowledge from various sources to identify research gaps and strengthen the theoretical foundation for future studies. The findings of this review emphasize that students’ etiquette, social relationships, and psychological conditions are integral aspects in building a healthy and sustainable educational system.